Kualitas Produk terhadap Kepercayaan: Peran Mediasi Citra Merek Pelanggan BLP Beauty pada Mahasiswa Institut STIAMI - Abdul Gofur (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
The purpose of this study was to examine the effect of product quality on trust both directly and indirectly by mediating brand image. Methodology The population of this research is STIAMI students who are customers of BLP Beauty products. The sample size of 100 was given a questionnaire by as far as possible the researchers and respondents on campus. Confirmatory factor analysis, reliability, descriptive, correlation and assumption tests were carried out. Hypothesis testing using process v3.5 model 4. Findings of the study prove that there is an indirect effect of product quality on trust through brand image mediation. Product quality has a positive effect on brand image and brand image positively affects customer trust. Suggestions for producers to pay attention to and improve the brand image of their products can be by improving product quality.